2008
DOI: 10.1124/jpet.107.132928
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Phosphorylation of Soluble Guanylyl Cyclase by Muscarinic m2 Receptors via Gβγ-Dependent Activation of c-Src Kinase

Abstract: In gastrointestinal smooth muscle, cGMP levels in response to relaxant agonists are regulated by activation of phosphodiesterase 5 and inhibition of soluble guanylyl cyclase (sGC) in a feedback mechanism via cGMP-dependent protein kinase. The aim of the present study was to determine whether contractile agonists modulate cGMP levels by cross-regulating sGC activity. In gastric muscle cells, acetylcholine (ACh) stimulated Src activity and induced sGC phosphorylation. Concurrent stimulation of cells with ACh att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The participation of G␣i-and G␤␥-subunits was investigated by transient transfection expression of either a cDNA minigene encoding the last COOH-terminal 11 amino acids, which block the effects mediated via G␣i or expression of cDNA encoding a G␤␥-scavenging peptide, which blocks the effects mediated via G␤␥ as described previously (21,28). The oligonucleotide sequence corresponding to the COOH-terminal 11-amino-acid residues of G␣i in random order was synthesized and ligated into pcDNA 3.1(ϩ) as a control scrambled sense minigene.…”
Section: Isolation Of Intestinal Muscle Cells From Human Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…The participation of G␣i-and G␤␥-subunits was investigated by transient transfection expression of either a cDNA minigene encoding the last COOH-terminal 11 amino acids, which block the effects mediated via G␣i or expression of cDNA encoding a G␤␥-scavenging peptide, which blocks the effects mediated via G␤␥ as described previously (21,28). The oligonucleotide sequence corresponding to the COOH-terminal 11-amino-acid residues of G␣i in random order was synthesized and ligated into pcDNA 3.1(ϩ) as a control scrambled sense minigene.…”
Section: Isolation Of Intestinal Muscle Cells From Human Intestinementioning
confidence: 99%
“…Activation of specific G proteins was determined from IGFBP-5-induced increase in G␣ binding to guanosine 5Ј-O-(3-thiotriphosphate) (GTP␥S) as described previously (16,21). Cells were homogenized in 20 mM HEPES (pH 7.4); the homogenates were centrifuged at 4°C for 30 min at 30,000 g; and the membranes were solubilized in 20 mM HEPES buffer containing 0.…”
Section: Isolation Of Intestinal Muscle Cells From Human Intestinementioning
confidence: 99%
“…Evidence [41], [50] suggests that Gβγ subunits initiate intracellular signalling cascades via the activation of PI3K [38]. It has been considered for some time that class IB PI3Ks can be activated by Gβγ dimers [51], [52].…”
Section: Discussionmentioning
confidence: 99%
“…1A). The COOH-terminal sequence of GRK2 acts as a specific G␤␥ (but not G␣) antagonist by binding to G␤␥ and blocking its interaction with effectors such as GRK2 (14,16,18,38). Treatment of freshly dispersed smooth muscle cells with DPDPE also stimulated cSrc phosphorylation, which was abolished in smooth muscle cells pretreated with the cSrc inhibitor PP2 or the PI 3-kinase inhibitor LY294002 (Fig.…”
Section: Dpdpe-stimulated Phosphorylation Of Csrc Mediated By G␤␥-depmentioning
confidence: 99%
“…Previous studies using freshly dispersed or cultured gastric smooth muscle cells, a model system used extensively to explore G protein-coupled receptor signaling in visceral smooth muscle, have shown that receptors coupled to G i1 [e.g., somatostatin (sstr 3 )] (21), G i2 (e.g., -, ␦-, and -opioid) (23), or G i3 (e.g., adenosine A 1 ) (22) induce contraction by activating dual signaling pathways initiated by G␤␥ (8): the first pathway involves activation of PLC␤ 3 , stimulation of inositol 1,4,5-trisphosphate-dependent Ca 2ϩ release, and phosphorylation of myosin light chain 20 (MLC 20 ), resulting in a transient smooth muscle contraction. The second pathway involves sequential activation of PI 3-kinase and ILK: the latter acts as a Ca 2ϩ -independent MLC kinase and inhibits MLC phosphatase (PP1c␦), resulting in sustained MLC 20 phosphorylation and smooth muscle contraction (5,8). In the present study we examined the significance of a parallel pathway initiated by these receptors and by G i3 -coupled muscarinic m 2 receptors involving sequential activation of G␤␥, PI 3-kinase-␥, and cSrc.…”
mentioning
confidence: 99%